The Phenomenon of Emergence as a Key to Deepening the Mystery of the Cosmos, for Cross-Disciplinary and Humble Scientific Research - Mantini, Alessandro (Religions, 2024)
The purpose of this article is to give a historical and reasoned overview of the phenomenon of emergence according to the various authors involved, with particular emphasis on its openness to the dimension of the mystery of the real, which can lead the scientist to humility in scientific research. The evidence, the curiosity and then the study of this concept, which is so pervasive in the complexity of cosmic dynamics, in fact requires an investigation that must be extended not only to different disciplines, but through them. In fact, the cross-disciplinary method enriches the quality of this research, giving reason to both the unity and the complexity of reality. The phenomenon of emergence is particularly concerned with this cross-disciplinary scientific approach, which transcends any reductionism in favour of a network of meanings specifically nourished by the possibility of conjunctive explanations involving empirical science, philosophy, metaphysics and theology. Faced with this perspective offered by emergence, science discovers the mystery of the cosmos in a new light, thereby opening the door to an ever deeper understanding and new avenues of research. An essential characteristic of this revised scientific method, inspired by cross-disciplinarity, is thus humility, which allows, on the one hand, a deeper relationship between disciplines and persons and, on the other hand, a heightened awareness of the depth of reality, as a complex and intelligible gift of a Trinitarian God, revealed as Logos in Jesus Christ.